If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4x-18=8x+6
We move all terms to the left:
-4x-18-(8x+6)=0
We get rid of parentheses
-4x-8x-6-18=0
We add all the numbers together, and all the variables
-12x-24=0
We move all terms containing x to the left, all other terms to the right
-12x=24
x=24/-12
x=-2
| -x+9=5x+9 | | 2s+2-5=5 | | 3.4r+.08=11 | | 7(x+3)+4(x-1)=8 | | 1.3+.5x=-341 | | D/12d=6d+24 | | 7x-3+7x-3+5x+5x=36 | | 257=-u+180 | | 25=2x5 | | -25=4x=-5 | | 7x+3=-4x-19 | | 1/3x=-1/4x-10. | | 6+x=15x= | | 4y−2=22 | | 14=8-4x+22 | | -3(n-5)=(-9 | | 12=v/4+9 | | D=9/2(m-67) | | 49x+23=65 | | 28=4g-5+5 | | 12*n=-1 | | 10(x-12)=200 | | -3n(n-5)=(-9) | | -5×-16+3=8x-3 | | 6y+1=y-9 | | 5x-9=160 | | 34-3.8x=-5.8x | | 56+7y=14y | | 5x-13x-5x=-13 | | -91=6a+5(1+6a) | | 5x+17=8x-13 | | 4x+5=−3 |